2021
DOI: 10.1002/adsp.12103
|View full text |Cite
|
Sign up to set email alerts
|

A Metastudy of Adultspan Journal : An Analysis of Publication Characteristics From 1999 to 2019

Abstract: Articles published in Adultspan Journal from 1999 to 2019 were analyzed for trends over time in author characteristics (e.g., leading contributors and institutions, work setting, gender, domicile) and article characteristics (e.g., reporting standards, topics, research design, participant characteristics, and statistical sophistication).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The growing overall proportion of research to nonresearch articles was impressive as the proportion of JCD research articles nearly doubled over the past 2 decades, increasing from 41.3% in 2000–2004 to 76.3% in 2015–2019. Not surprisingly, this trend toward more published research articles was noted in recent metastudies of many other counseling family journals, including Adultspan Journal (Rippeto et al, 2021), CES (Johnsen et al, 2021); CORE (Johnson et al, 2021), CVJ (Alder et al, in press), JAOC (MacInerney et al, 2020), JCC (Milowsky et al, in press), JMHC (Menzies et al, 2020), and MECD (Saks et al, 2020). Indeed, several counseling family journals are now close to or exceeding an 80% threshold of published research articles (i.e., CES, CORE, JCC , and MECD ).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The growing overall proportion of research to nonresearch articles was impressive as the proportion of JCD research articles nearly doubled over the past 2 decades, increasing from 41.3% in 2000–2004 to 76.3% in 2015–2019. Not surprisingly, this trend toward more published research articles was noted in recent metastudies of many other counseling family journals, including Adultspan Journal (Rippeto et al, 2021), CES (Johnsen et al, 2021); CORE (Johnson et al, 2021), CVJ (Alder et al, in press), JAOC (MacInerney et al, 2020), JCC (Milowsky et al, in press), JMHC (Menzies et al, 2020), and MECD (Saks et al, 2020). Indeed, several counseling family journals are now close to or exceeding an 80% threshold of published research articles (i.e., CES, CORE, JCC , and MECD ).…”
Section: Discussionmentioning
confidence: 79%
“…The number of authors credited for each article has grown steadily over the past 20 years from 2.27 authors per JCD article in 2000–2004 to 3.18 authors per article in 2015–2019. This trend of multiple authorship is also apparent in other counseling journals, including Adultspan Journal (Rippeto et al, 2021), CORE (Johnson et al, 2021), CVJ (Alder et al, in press), JAOC (MacInerney et al, 2020), JCC (Milowsky et al, in press), JMHC (Menzies et al, 2020), and MECD (Saks et al, 2020). Previously, Erford et al (2011) found that JCD authorship also reflected this trend, and recent growth suggests an expanded author collaboration, and perhaps mentorship, culture in the last decade.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations